What should make returning leagues shut down for COVID-19? - Binney, Z. (Emory Univerity, 2020)
With many U.S. sports leagues proposing return plans in a country with ongoing rampant spread of COVID-19, everybody (well, every journalist who interviews the autor) is wondering "What`s the red line? What would mean they have to shut down again?" The author has been revising and polishing his thoughts as he talks with journalists and colleagues. Here`s a summary of his current thinking.